A Review on concept of Mutravruddhi - Padadharia, Dhruval; sharma, Rajesh Kumar; Shah, Harshit; sharma, Varsha; Parmar, Damini (Asian Journal of Pharmaceutical Research and Development, 2023)
Mutravrdidhi is one of the most common type of Vriddhiroga. When one of the vitiated dosha travels downward in the phalakoshvahini and produce giant swelling is known as vrudhhi. Due to mutravegadharan, mutra accumulates and reaches to phalakosha which leads to mutravruddhi. Acharyas mentioned shastra karma for management of mutravriddhi. Mutravridhi can be compared to hydrocele. A hydrocele is a collection of serous fluid between the two layers of the tunica Vaginalis which normally surrounds the testis. This is the most common benign scrotal swelling and has been estimated to occur in as many as 1% of the adult male population.A change in scrotal size can be a Disturbing physical change for any adult male. Scrotal pain during intercourse of physical activity; Discomfort related to the enlarged scrotum, cosmetic appearance of the scrotum, concerns of the damage to the reproductive organs or possible malignancy are reasons why men sick evaluation for any increase in scrotal size. Hydrocele may also develop in boys and adult men due to any injury or inflammation within the scrotum. In management of mild hydroceles scrotal support is generally recommended. In severe condition surgical drainage required. The treatment of choice in hydrocele is surgical intervention.